2023
DOI: 10.21203/rs.3.rs-2401406/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimating plastic pollution levels in rivers through harmonized monitoring strategies

Abstract: Plastic pollution in freshwater environments is an emerging threat to ecosystem health and human livelihood. Plastics that accumulate in rivers and lakes over long time periods have direct local impact, and may eventually also reach the world’s oceans. Monitoring river plastic pollution is therefore key to quantify, understand and reduce plastics in all aquatic ecosystems. Unfortunately, global river plastic monitoring is still in its early stage. The lack of harmonization between ongoing monitoring efforts co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In the Seine, plastic transport increased with a factor ten when discharge increased only a factor three (van Calcar and van Emmerik, 2019). A recent study in the Meuse found a power law relation between discharge and plastic transport, suggesting a non-linear response of plastic transport to discharge (van Emmerik et al, 2022b). The disproportional increase of plastic transport to discharge is generally explained by additional mobilization of plastic towards the river, and remobilization of accumulated plastics on the riverbanks and floodplain due to increased water level and flow velocities.…”
Section: Difference Between Wet and Dry Seasonmentioning
confidence: 89%
See 3 more Smart Citations
“…In the Seine, plastic transport increased with a factor ten when discharge increased only a factor three (van Calcar and van Emmerik, 2019). A recent study in the Meuse found a power law relation between discharge and plastic transport, suggesting a non-linear response of plastic transport to discharge (van Emmerik et al, 2022b). The disproportional increase of plastic transport to discharge is generally explained by additional mobilization of plastic towards the river, and remobilization of accumulated plastics on the riverbanks and floodplain due to increased water level and flow velocities.…”
Section: Difference Between Wet and Dry Seasonmentioning
confidence: 89%
“…Not all methods are however suitable to be applied during extreme flow conditions. During floods, large debris and debris patches can make net sampling challenging and dangerous, both from boats or bridges (van Emmerik et al, 2022b). Visual counting from bridges or imagebased techniques provide a safe alternative.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations